The Influence of Teacher Certification and Teaching Motivation on Teacher Performance - Taryana Taryana; Wa Ode Riniati; Gamar Al Haddar; Muthia Mutmainnah; Darmawanta Sembiring (Journal on Education, 2023)
This study aims to find out how these three components are related and influence each other. This study specifically analyzes the effect of teacher certification and teacher motivation on teacher performance in several Islamic elementary schools in South Jakarta. This study uses a regression analysis method with a quantitative approach. The quantitative method was chosen to be used in this study because the specifications of this design were systematic, planned, and clearly structured from the start of the creation of the research design. This research will also take a descriptive approach in order to adequately describe the research object or research results. The population in this study are teachers who have received a teacher certification allowance for at least five years and have had teaching experience for approximately ten years. Based on research data and discussion regarding the effect of teacher certification and teacher work motivation on teacher performance at Madrasah Ibtidaiyah as KKMI Kebayoran Lama, the following conclusions can be drawn: First, teacher certification has a partially positive effect on teacher performance. This is indicated by the value of the X1 regression coefficient of 1,401, which states that every 2 percent increase in teacher certification will increase teacher performance by 1,401 percent. The probability value is less than 5%, namely 0.000 < 0.05 indicating that teacher certification has a positive effect on teacher performance. Second, teacher work motivation partially has a positive effect on teacher performance.